A simplified constitutive model for corroded steel bars. (20th October 2018) - Li, Dawang; Xiong, Cheng; Huang, Tong; Wei, Ren; Han, Ningxu; Xing, Feng
Highlights: A theoretical constitutive model is developed to describe the mechanical properties of corroded steel bars. The proposed model is validated using experimentally obtained stress-strain curves of corroded steel bars. The model describes how the ductility of corroded steel bars varies with the corrosion level. A definition on the "light" and "heavy" corrosion is proposed based on the present model. Abstract: In this paper a theoretical constitutive model is developed to describe the mechanical properties of corroded steel bars. The model is established based on the assumption that the effect of corrosion on the steel bars only leads to the local reduction of cross-section area of the steel bars. By using a bilinear elastoplastic constitutive equation, a generalized equivalent stress-strain equation is derived for the corroded steel bars, which considers the pitting corrosion nature. The derived stress-strain equation is validated using experimental data. To demonstrate the features of the stress-strain equation, a parametric study is also presented.